Dinamika Perkawinan Beda Agama dalam Perspektif Hukum Keluarga Islam dan Implikasinya di Indonesia - Abdurrahman Hakim; Agus Putrono; Andri Setiawan (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the dynamics of interfaith marriages in Indonesia from the perspective of Islamic family law, as well as examine its implications for family and community life. This research uses a qualitative approach with a case study method and document analysis. Data were collected through in-depth interviews with interfaith couples, religious leaders, and legal practitioners, as well as analysis of legal documents and court decisions. The theories used include Islamic family law theory, legal pluralism theory, and social conflict and integration theory. The results show the complexity in the practice of interfaith marriage, with various challenges and adaptation strategies carried out by couples. The legal, social, and religious implications of these marriages are also discussed, as well as recommendations for improving regulations and increasing public understanding.